2014
DOI: 10.1371/journal.pone.0094585
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HDL-Raising Drugs on Cardiovascular Outcomes: A Systematic Review and Meta-Regression

Abstract: BackgroundSubstantial residual cardiovascular risk remains after optimal LDL lowering in patients of established coronary artery disease. A number of therapeutic agents that raise HDL-C have been tested in clinical trials to cover this risk. However, the results of clinical trials are conflicting.ObjectivesTo determine whether raising HDL-C with pharmacologic therapies translates into beneficial cardiovascular outcomes and to find out if this change was proportional to the percentage change in HDL levels.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…212 To date, clinical trials of agents that markedly raise HDL-C, including niacin and cholesteryl ester transfer protein inhibitors, have failed to demonstrate that they reduce all cause mortality, CHD mortality, myocardial infarction, or stroke in statin-treated patients. 210,[213][214][215][216][217] The NLA Expert Panel did not rule out the possibility of a potential ASCVD risk-reduction benefit with raising HDL-C or promoting HDL function, but at this time, HDL-C is not recommended as a target of therapy per se. The HDL-C level is often raised as a consequence of efforts to reduce atherogenic cholesterol through lifestyle and drug therapies.…”
Section: Triglyceridesmentioning
confidence: 99%
“…212 To date, clinical trials of agents that markedly raise HDL-C, including niacin and cholesteryl ester transfer protein inhibitors, have failed to demonstrate that they reduce all cause mortality, CHD mortality, myocardial infarction, or stroke in statin-treated patients. 210,[213][214][215][216][217] The NLA Expert Panel did not rule out the possibility of a potential ASCVD risk-reduction benefit with raising HDL-C or promoting HDL function, but at this time, HDL-C is not recommended as a target of therapy per se. The HDL-C level is often raised as a consequence of efforts to reduce atherogenic cholesterol through lifestyle and drug therapies.…”
Section: Triglyceridesmentioning
confidence: 99%
“…Findings suggest that approximately half of the lower CAD risk in drinkers is mediated by higher HDL levels [38,43] and that major HDL subfractions, known as HDL 2 and HDL 3 , are involved [44]. The failure of HDL-raising medications to have a beneficial effect [45] and more sophisticated characterization of HDL subfractions [46] have raised questions about the likelihood of a simplistic interpretation [47]. Nevertheless, the HDL link remains the best established mechanism to explain the beneficial effect of alcohol on CAD.…”
Section: Mechanisms To Explain the Lower Cad Risk In Drinkersmentioning
confidence: 99%
“…However, treatments other than ezetimibe for further management of hyperlipidemia and risk reduction have failed to demonstrate consistent benefi t when added to statin therapy. [15][16][17][18][19] The largest studies were with niacin and fi brates. Unfortunately, most trials demonstrated no overall outcomes benefi t or only benefi ts in subgroup analyses, leaving the door open to other pharmacologic interventions.…”
Section: Patients With Side Effects To Statins Particularlymentioning
confidence: 99%